The prevalence of low back pain and its relationship with BMI, age, level of education and ergonomic principles education among rural women - Hossien Izadirad; Iraj Zareban; Gholamreza Masoudy (Mashhad University of Medical Sciences, 2017)
Background and objective: Low back pain in addition to individual conditions reduced working capacity, a waste of time, absence from work, increased healthcare costs and economic losses. The present study was conducted to determine the prevalence of low back pain and its relationship with BMI, age, level of education and ergonomic principles education among rural women of Aq Qala city in 2016. Methods: This present cross sectional descriptive study was conducted on 215 women from the village of the Aq Qala city. Data were collected by the Nordic questionnaires. The data was analyzed with software spss20, chi-square test and descriptive statistics. Results: The prevalence of low back pain was 81/86% among rural women . χ2 analysis showed a significant relationship between low back pain with BMI(p=0/004), age(p=0/045) and education of ergonomic principles (p=0/003). There is no relationship between low back pain with level of education (p=0/08). Only 8/37% of participants were trained on ergonomic principles. Conclusion: Considering the high prevalence of low back pain, The need  felt for training these people in the field of weight loss, Implementation of ergonomic principles in Home working and Agriculture activities. Paper Type: Research Article.